From Welcoming Newly Arrived Migrant Students to Creating an Inclusive and Hospitable Environment: The Proposal from the Universe School - Mar Badia Martín; Adriana Devant Cerezo (MDPI AG, 2024)
In Catalan schools, the rising influx of newly immigrated students poses significant challenges concerning their inclusion. These students show lower academic performance and self-esteem, are more likely to engage in risky behaviors, and lack support as they cope with the mourning process of migrating. Implementing intercultural education, working on socio-emotional skills, and helping to build a support network can be protective factors in improving the students' development. This project was implemented in a Barcelona public school and aimed to identify the needs of newcomer students and enhance their inclusion. A questionnaire administered to 30 teachers revealed low knowledge about migratory mourning and intercultural education. Consequently, training sessions addressed to the school's teaching staff were developed to provide them with the necessary knowledge and skills to deal with these topics. Interviews were conducted with the newly arrived children, specifically with 12 of them. They revealed a need for emotional support, the presence of migratory mourning, and a lack of a support network and socio-emotional skills. Students have appreciated the active listening and the opportunity to share their migration process. Teachers feel more empowered to support students in the migration mourning process after the training sessions. Feedback after the training sessions highlighted the clarity, ease of understanding, and usefulness of the material shared positively. The project lays the groundwork for more inclusive and intercultural initiatives in the school. Integrating the provided training into the teacher training curriculum could have a significant impact, better equipping educators to support recently arrived migrant students.